DEMOCRACY EDUCATION THE DIALOGOS WAY: THE CASE OF UKRAINEAN TEACHER EDUCATION - Hansen Helskog, Guro (Професіоналізм педагога: теоретичні й методичні аспекти, 2019)
This paper takes its point of departure in action learning- and research carried out with teacher educators from six universities within the project Democracy Education in Ukraine, Norway and Palestine. The teacher educators received training in accordance with the Dialogos approach to dialogical philosophizing, and tried out the approach with colleagues and/or with students in their own teaching practices. However, the main concern of the article is the discussion the potential of action learning and action research in teacher education when it comes to the development of phronesis or practical wisdom as an element in democracy education. Democracy Education the Dialogos Way is part of the project Democracy Education in Ukraine, Norway and Palestine. The author stresses that the results of the project can be studied from many perspectives. In accordance to the author’s point of view, it is relevant to see the project as a new step in the bigger action research project work to justify and show the relevance of the Dialogos approach, regarding the enhancement of democratic ways of living together in a shared world. Important in this respect, is that edification towards wisdom and prudence cannot be taught directly. It requires active participation from the student, a will to wisdom and a willingness to put his or her horizon of understanding into play in the educational situation. It requires teacher educators who are willing to do the same. The teacher educators and the students are in the philosophical dialogues as well as in the action research together. The author describes how she let Socrates speak through the written dialogue of Plato’s Republic. The author concluded that according to Socrates the faculty of sight already exists in the human being. It needs only to be re-awakened. Key words